The Influence of Customer Trust on Salwa Minimarket Customer Loyalty with Customer Commitment as a Moderating Variable - Khamdan Suriyok; Arif Syaifudin (Enrichment : Journal of Management, 2023)
Based on the results of interviews with several customers of "Minimarket Salwa" in "Minimarket Salwa" in Dukun Gresik District, there were several problems, such as the lack of service when entering there was no greeting like other Minimarkets because they were left joking with friends, food shelves which looks messy and untidy, so that customers are less loyal to shopping at the Minimarket. Several other things make customers disloyal to the Minimarket, such as the incompatibility of the prices of goods on the display rack with the cashier's computer, plus the absence of prices listed when the cashier scans the goods, the inaccuracy of employees regarding expired items that have not been replaced with new ones. The fourth case is change which is often exchanged for candy. The population in this study is "Minimarket Salwa" customers, Purposive Sampling Sampling Technique 40 customers. The results of the research show that the variable Customer Trust has a significant effect on Customer Loyalty. Customer Trust moderated by customer commitment shows no significant effect on customer loyalty.